Evaluation of a safe medication strategy intervention for people with dementia with an unplanned admission: Results from the Safe Medication Strategy Dementia Study. (9th November 2020) - Kable, Ashley; Hullick, Carolyn; Palazzi, Kerrin; Oldmeadow, Christopher; Searles, Andrew; Ling, Rod; Pond, Dimity; Fullerton, Anne; Fraser, Samantha; Bruce, Remia; Murdoch, Wendy; Attia, John
Abstract: Objective: To evaluate whether a safe medication strategy compared with usual care, provided to people with dementia during an unplanned admission, reduces readmissions to hospital and re‐presentation to emergency departments within three months. Methods: A prospective, controlled pre‐/post‐trial conducted at two regional hospitals in New South Wales, Australia. Results: No treatment effect was seen for time to first re‐presentation or readmission within three months ( P  = .3). Compliance with six strategies applicable for all participants in the intervention phase was 58%. There was no treatment effect for secondary outcomes including dose administration aid use, home medicines review (HMR) requests by general practitioners and completed HMRs; however, they were significantly higher at the intervention site in both phases. Conclusion: A bundle of care to improve medication safety in people with dementia did not reduce re‐presentations or readmissions within three months.